Peran Manajemen Risiko dalam Meningkatkan Kinerja Mesin Filling Emulsion dengan Pendekatan House of Risk (HOR) - Muhammad Fauzan; Bagus Jati Santoso (Benefit: Jurnal Manajemen dan Bisnis, 2024)
In the competitive paint industry, improving operational performance is crucial for achieving excellence. The filling process plays a key role in determining the quality and safety of the final product. Filling machines ensure consistency and accuracy in paint filling, as well as high productivity. To prevent downtime that could lead to breakdowns, optimal maintenance is necessary. Autonomous Maintenance (AM), a key pillar of TPM, aims to enhance machine effectiveness and minimize downtime, but it is often hindered by the lack of adequate risk management. This study aims to optimize the AM system on emulsion filling machines using the House of Risk (HOR) approach to identify and address priority risks. Risks are analyzed using Failure Mode and Effect Analysis (FMEA) to assess their impact and probability, leading to the formulation of effective prevention strategies. HOR helps reduce the likelihood of negative risks and provides better preventive recommendations, ultimately improving AM effectiveness and the company’s operational performance. Keywords: Autonomous Maintenance, House of Risk, Downtime, Filling machine.